2010
DOI: 10.1111/j.1365-2648.2009.05217.x
|View full text |Cite
|
Sign up to set email alerts
|

Huntington disease: families’ experiences of healthcare services

Abstract: Aim This paper is a report of a study of the perceptions of family caregivers regarding the availability and adequacy of health and social care services for their family member with Huntington disease, and to compare findings from these reports in United Kingdom and United States of America samples. Background Huntington disease is an inherited neurodegenerative condition. Family members often take responsibility for care of relatives with long-term conditions. Studies have demonstrated there are both positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 22 publications
(24 reference statements)
1
25
0
Order By: Relevance
“…Self-reported quality of life among caregivers of individuals with HD is similar to that of patients 18. The reasons for this significant impact on caregivers may reflect the fact that family caregivers provide the majority of skilled care for individuals with HD; are in the unique position of having to worry about the risk of illness on future generations; are children of the affected patient, not emotionally equipped to take on this role reversal; may lack the knowledge necessary to navigate a complicated disease process; and that HD affects patients in their prime of life, causing significant financial strain and a drastic adjustment in family dynamics, lifestyle, and expectations 2527. Despite these challenges, caregivers willingly take on these roles with the relentless and often unexpected demands having a significant impact on caregiver quality of life 17…”
Section: Caregiver Burdenmentioning
confidence: 99%
“…Self-reported quality of life among caregivers of individuals with HD is similar to that of patients 18. The reasons for this significant impact on caregivers may reflect the fact that family caregivers provide the majority of skilled care for individuals with HD; are in the unique position of having to worry about the risk of illness on future generations; are children of the affected patient, not emotionally equipped to take on this role reversal; may lack the knowledge necessary to navigate a complicated disease process; and that HD affects patients in their prime of life, causing significant financial strain and a drastic adjustment in family dynamics, lifestyle, and expectations 2527. Despite these challenges, caregivers willingly take on these roles with the relentless and often unexpected demands having a significant impact on caregiver quality of life 17…”
Section: Caregiver Burdenmentioning
confidence: 99%
“…Despite numerous recommendations for increased and tailored HD carer support (Skirton et al, 2010;Dawson et al, 2004;Soltysiak et al, 2008;Williams et al, 2012;Hartelius et al, 2010), there is a paucity of research describing specific interventions for HD carers and evaluation studies of such interventions. One paper identified that an HD day service was felt to be supportive to carers, promote their well-being and allow respite for them (Soltysiak et al, 2008).…”
Section: Introductionmentioning
confidence: 96%
“…The rarity of the disease can result in HD families not always having access to specialist HD healthcare providers. In a survey of HD carers in the UK and USA, it was found that there were concerns about the extent of knowledge among healthcare staff and that more support services were required for HD families (Skirton et al, 2010). The lack of understanding about HD among medical professionals was reported to be a major stress for carers of HD patients (Roscoe et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, in the latter stages of disease, nursing home facilities and end-stage palliative care are often required, as caregiver burden and quality of life become major concerns 5 .…”
mentioning
confidence: 99%